2009
DOI: 10.2139/ssrn.1396943
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Shocks and Their Short- and Long-Term Effects on the Chinese Economy

Abstract: A considerable body of economic literature shows the adverse economic impacts of oil-price shocks for the developed economies. However, there has been a lack of empirical study of this kind on China and other developing countries. This paper attempts to fill this gap by answering how and to what extent oil-price shocks impact China's economy, emphasizing on the price transmission mechanisms. To that end, we develop a structural vector auto-regressive model. Our results show that an oil-price increase negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 29 publications
5
71
1
1
Order By: Relevance
“…On one hand, higher oil prices exert negative impacts on the economy, such as lower productivity and/or higher inflation (see, inter alia, Filis and Chatziantoniou, 2013;Montoro, 2012;Natal, 2012;Rahman and Serletis, 2011;Balke et al, 2010;Elder and Serletis, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Cologni and Manera, 2008;Cunado and Pérez de Gracia, 2005;Peter Ferderer, 1997;Hamilton, 1983). Such economic conditions put pressure on policy makers to mitigate the negative effects of increased oil prices, which in turn, raises concerns regarding the success of these policies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, higher oil prices exert negative impacts on the economy, such as lower productivity and/or higher inflation (see, inter alia, Filis and Chatziantoniou, 2013;Montoro, 2012;Natal, 2012;Rahman and Serletis, 2011;Balke et al, 2010;Elder and Serletis, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Cologni and Manera, 2008;Cunado and Pérez de Gracia, 2005;Peter Ferderer, 1997;Hamilton, 1983). Such economic conditions put pressure on policy makers to mitigate the negative effects of increased oil prices, which in turn, raises concerns regarding the success of these policies.…”
Section: Resultsmentioning
confidence: 99%
“…Since the seminal paper by Hamilton (1983), mounting empirical evidence indicates that oil prices exercise a strong negative influence on the economy. More specifically, past evidence suggest that there are significant effects of oil prices on industrial production and inflation (see, inter alia, Filis and Chatziantoniou, 2013;Balke et al, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Peter Ferderer, 1997). Furthermore, authors such as, Rahman and Serletis (2011), Elder and Serletis (2010), Cologni and Manera (2008), Cunado and Pérez de Gracia (2005), Lee et al (1995) and Hamilton (1983) confirm that the US economic activity has been significantly affected by rises in oil prices, as well as, by the uncertainty about future oil price changes.…”
Section: Introductionmentioning
confidence: 95%
“…They applied a structural vector autoregression model (SVAR) and confirmed that oil price leadsto a current account deficit that leads to a decline in economic growth. In the case of China, Tang et al (2010) reported that oil price shocks adversely affect economic growth and investment.…”
Section: Oil Price and Economic Growthmentioning
confidence: 99%
“…Oil prices hike affect real economic activity via supply and demand channels and vice versa. The supply-side channel reveals that oil is a basic factor for production, and an increase in oil price lead to increase in the cost of production, which leads firms or industries to lower output (Morey 1993, Tang et al 2010. The demand-side channel entails that oil price shocks affect not only consumption but also investment activities.…”
Section: The Model and Datamentioning
confidence: 99%
See 1 more Smart Citation